ANALISIS PENGELOLAAN PANGKALAN PENDARATAN IKAN (PPI) LERO DI DESA WIRINGTASI KECAMATAN SUPPA KABUPATEN PINRANG - Syamzam Syamzam; Danial Danial; Ihsan Ihsan (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
This study aims to determine the current conditions, examine the utilization of facilities and infrastructure for the Lero Fish Landing Base (PPI) and its development; and formulate a management strategy. This research was carried out from March to June 2021 at the Lero Fish Landing Base (PPI). The research method is observation and interview. Determination of the sample by purposive sampling, the number of respondents 48 people. Data were analyzed descriptively, using utilization rate analysis and SWOT analysis. The results of the study show: 1) The current condition of PPI Lero's facilities and infrastructure is in poor to very good condition, it is necessary to manage its utilization and develop human resources; 2) Utilization of facilities and infrastructure of PPI Lero obtained a percentage of <100% or has not reached optimal, it is necessary to build a breakwater and SPDN; 3) PPI Lero by utilizing existing strengths to seize opportunities as much as possible so that it can establish cooperation between the Government and private companies in its management so as to improve the welfare of the community.